Insegurança alimentar, estado nutricional e consumo alimentar de crianças e adolescentes residentes em uma área de vulnerabilidade social do município de Palmas - TO - Pereira, Ana Caroline Fernandes (Universidade Federal do Tocantins, 2023)
It is observed that children and adolescents are more vulnerable to food insecurity, because children exposed to this reality are at greater risk of being affected by their growth and development. This study was conducted in order to investigate the relationship between nutritional status, food consumption and food insecurity of children and adolescents living in an area of social vulnerability in the city of Palmas - TO. This is a cross-sectional study with 15 children and adolescents belonging to 10 families accompanied by the Association of Women in Palme Action - TO (AMAP). Socioeconomic aspects, food (in)security, nutritional status and food consumption of children and adolescents were evaluated. The nutritional status and food consumption of children and adolescents showed no significant relationship with socioeconomic and food security data. However, it was found that families had different aspects of socioeconomic vulnerability, which can negatively interfere with both the nutritional status and food consumption of children and adolescents. In view of this, studies such as this one are of great relevance to relate the determinants of Food and Nutrition Security (FNS), in order to then develop interventions with more resolutiveness for the community.